Institutional Dynamics of the EU After Maastricht (1993–2023): Separation of Powers As an Old Principle of Constitutionalism in New Circumstances - Bačić, Petar (Maastricht 30: A Central European Perspective, 2025)
In this paper, the author investigates the issue of the separation of powers in the institutional network of the European Union, bearing in mind that it represents an inseparable part of the materiae constitutionis of democratic constitutionalism. Since Montesquieu, the goal of this principle has been nothing but to realise, preserve and strengthen the lawful government (government of law) instead of maintaining anddefending a gubernaculum as the mere will and caprice of the holder of power (car tel est notre plaisir). Therefore, it is a legitimate assumption that the doctrine of the separation of powers, which plays a key role in the creation of any political government, especially in the functioning of and respect for a just, lawful and independent judicial authority within the nation-state, mutatis mutandis would seek its place across state borders as well. This possibility is also indicated by the construction of the Maastricht Treaty (1992) which, by constitutionalising the EU’s institutional structure, certainly opened not only a new stage in the adaptation of its organisational principles, but it once again shed new light on the question of the existence, state, adjustment, design, new content and understanding of the separation of powers as an old principle of constitutionalism under new circumstances.Keywords: Maastricht Treaty, institutions, separation of powers, institutional balance